Staphylococcus aureus in animals - Haag,AF; Ross,Fitzgerald J; Penadés,JR (2019)
The genus Staphylococcus currently comprises 81 species and subspecies (https://www.dsmz.de/bacterial-diversity/prokaryotic-nomenclature-up-to-date/prokaryotic-nomenclature-up-to-date.html), and most members of the genus are mammalian commensals or opportunistic pathogens that colonize niches such as skin, nares, and diverse mucosal membranes. Several species are of significant medical or veterinary importance. Staphylococcus pseudintermedius (1) is a leading cause of pyoderma in dogs and is considered to be a significant reservoir of antimicrobial resistance factors for the genus (2, 3). S. pseudintermedius is very similar to Staphylococcus intermedius and can be distinguished from other coagulase-positive staphylococci by positive arginine dihydrolase and acid production from β-gentiobiose and d-mannitol (4) or by using a multiplex-PCR approach targeting the nuclease gene nuc (5). Staphylococcus saprophyticus is the second leading cause of uncomplicated urinary tract infections (6). While Staphylococcus epidermidis is a normal component of the epidermal microbiota, it is a leading cause of biofilm contamination of medical devices (7). The most promiscuous and most significant human pathogenic staphylococcal species is Staphylococcus aureus, which is the causal agent of a variety of disease symptoms that can range from cosmetic to lethal manifestations. S. aureus is distinguished from most members of the genus by its abundant production of secreted coagulase, an enzyme which converts serum fibrinogen to fibrin and promotes clotting. However, the S. intermedius group and some strains of Staphylococcus lugdunensis have coagulase activity (5, 8, 9).